Implementation of two-factor user authentication in computer systems - Tomić, Mihailo D.; Radojević, Olivera M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The paper explores the implementation of two-factor authentication (2FA) in computer systems, addressing the increasing need for enhanced security. It highlights the vulnerabilities of password-based authentication and emphasizes the advantages of 2FA in mitigating digital threats. The development of the VoiceAuth application, integrating 2FA through a combination of password and voice authentication, serves as a practical illustration.Methods: The research adopts a three-tier architecture for the VoiceAuth application, encompassing a database, server-side REST API, and client-side single-page application. Speaker verification is employed for voice authentication, analyzing elements like pitch, rhythm, and vocal tract shapes.The paper also discusses possibilities for future upgrades, suggesting enhancements such as real-time voice verification and additional 2FA methods.Results: The application's implementation involves a detailed breakdown of the REST API architecture, Single Page Applications (SPAs), and the Speaker Verification service.Conclusion: The research underscores the crucial role of two-factor authentication (2FA) in bolstering the security of computer systems. The VoiceAuth application serves as a practical demonstration, showcasing the successful integration of 2FA through a combination of password and voice authentication. The modular architecture of the application allows for potential upgrades.
Keywords: authentication; computer systems; biometrics